2014
DOI: 10.1371/journal.pone.0103174
|View full text |Cite
|
Sign up to set email alerts
|

Oligodendrocyte Precursor Cells Support Blood-Brain Barrier Integrity via TGF-β Signaling

Abstract: Trophic coupling between cerebral endothelium and their neighboring cells is required for the development and maintenance of blood-brain barrier (BBB) function. Here we report that oligodendrocyte precursor cells (OPCs) secrete soluble factor TGF-β1 to support BBB integrity. Firstly, we prepared conditioned media from OPC cultures and added them to cerebral endothelial cultures. Our pharmacological experiments showed that OPC-conditioned media increased expressions of tight-junction proteins and decreased in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
121
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(126 citation statements)
references
References 45 publications
(51 reference statements)
2
121
0
3
Order By: Relevance
“…Similar reports have demonstrated cross‐talk between secreted factors (e.g., apoptosis, inflammation, oxidative stress) (; Brill et al, 2009; Chapman et al, 2015; Lu, Jones, Snyder, & Tuszynski, 2003; Zhang et al, 2015) and neurogenesis following brain insults, including stroke (Kernie and Parent, 2010; Yamashita et al, 2006). We (Hara et al, 2007; Morimoto et al, 2011; Tajiri et al, 2013), and others, have shown the important contribution of neurogenic factors in stroke brain remodeling (Jablonska et al, 2016; Rosell et al, 2013; Seo et al, 2014; Venna, Xu, Doran, Patrizz, & McCullough, 2014). Altogether, these results allude to host neurogenesis and its secreted neurogenic factors as key therapeutic targets of NSI‐189 in affording behavioral and neurostructural benefits in stroke.…”
Section: Discussionmentioning
confidence: 87%
“…Similar reports have demonstrated cross‐talk between secreted factors (e.g., apoptosis, inflammation, oxidative stress) (; Brill et al, 2009; Chapman et al, 2015; Lu, Jones, Snyder, & Tuszynski, 2003; Zhang et al, 2015) and neurogenesis following brain insults, including stroke (Kernie and Parent, 2010; Yamashita et al, 2006). We (Hara et al, 2007; Morimoto et al, 2011; Tajiri et al, 2013), and others, have shown the important contribution of neurogenic factors in stroke brain remodeling (Jablonska et al, 2016; Rosell et al, 2013; Seo et al, 2014; Venna, Xu, Doran, Patrizz, & McCullough, 2014). Altogether, these results allude to host neurogenesis and its secreted neurogenic factors as key therapeutic targets of NSI‐189 in affording behavioral and neurostructural benefits in stroke.…”
Section: Discussionmentioning
confidence: 87%
“…25 It has been increasingly recognized that oligodendrocyte precursor cells themselves also play a pivotal role in promoting BBB integrity by the secretion of transforming growth factor-β1. 93 Moreover, electron microscopy has demonstrated that oligodendrocyte precursor cells and pericytes directly adhere to and communicate with each other via basal lamina to promote their proliferation and differentiation. 94 The above data implicate the impact of disrupted cross talk among BBB cell components in the development of disease pathology.…”
Section: Important Roles Of Cell Components Of Bbb In Svdmentioning
confidence: 99%
“…Некоторые из этих генов также были идентифицированы при анализе генома людей с ГБВГМ [25]. Было доказано, что клетки-предше-ственники олигодендроцитов сами по себе также играют ключевую роль в обеспечении целостности ГЭБ посред-ством секреции трансформирующего фактора роста-β1 [93]. Кроме того, посредством электронной микроскопии обнаружили, что клетки-предшественники олигодендро-цитов и перициты непосредственно прилегают друг к другу и взаимодействуют через базальную пластинку для обеспечения их пролиферации и дифференцировки [94].…”
Section: важная роль клеточных компонентов гэб при бмцсunclassified
“…The authors propose that TGF-b increases BBB integrity through activation of the MAPK/ERK pathway. 69 TGF-b may also be involved in many CNS disorders. AD patients show increased TGF-b levels in the brain, but decreased levels in serum (similar to amyloid b in AD).…”
Section: -60mentioning
confidence: 99%